2013
DOI: 10.1002/pen.23800
|View full text |Cite
|
Sign up to set email alerts
|

Polythiophene-based materials for nonvolatile polymeric memory devices

Abstract: Polymeric materials used in memory devices have attracted significant scientific interest due to their several advantages, such as low cost, solution processability, and possible development of three-dimensional stacking devices. Polythiophenes, including tethered alkyl substituted polythiophenes and block copolymers, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) and composites, are one of the most attractive polymeric systems for memory applications because of their commercial availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…One of the most attractive conjugated polymers to use as a core-forming block for living CDSA methods is poly­(3-hexylthiophene) (P3HT) as a result of its widespread use in organic optoelectronic devices. The self-assembly of amphiphilic P3HT BCPs has attracted much attention over the past decade. However, attempts to implement ambient temperature living CDSA methods with BCPs such as P3HT- b -PDMS (PDMS = poly­(dimethylsiloxane)) and P3HT- b -P2VP (P2VP = poly­(2-vinylpyridine)) only allowed length control up to ca. 250–300 nm as a result of competing homogeneous nucleation (which led to the formation of new fibers) and rapid crystallization, which appeared to introduce defects into the growing micelle core. , Performing self-seeding experiments at temperatures that reduce the propensity for homogeneous nucleation and slow the rate of crystallization allowed access to low-dispersity fiberlike micelles with a P3HT core of length up to 1000 nm .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most attractive conjugated polymers to use as a core-forming block for living CDSA methods is poly­(3-hexylthiophene) (P3HT) as a result of its widespread use in organic optoelectronic devices. The self-assembly of amphiphilic P3HT BCPs has attracted much attention over the past decade. However, attempts to implement ambient temperature living CDSA methods with BCPs such as P3HT- b -PDMS (PDMS = poly­(dimethylsiloxane)) and P3HT- b -P2VP (P2VP = poly­(2-vinylpyridine)) only allowed length control up to ca. 250–300 nm as a result of competing homogeneous nucleation (which led to the formation of new fibers) and rapid crystallization, which appeared to introduce defects into the growing micelle core. , Performing self-seeding experiments at temperatures that reduce the propensity for homogeneous nucleation and slow the rate of crystallization allowed access to low-dispersity fiberlike micelles with a P3HT core of length up to 1000 nm .…”
Section: Introductionmentioning
confidence: 99%
“…Determining of the charge transport mechanism in the materials such as conducting polymers and its composites is therefore central in improving device performance and/or designing new devices. For instance, Li and Shen denoted that the transport mechanism of PTh plays an important role in the performance of the polymer based memory devices. Kline and McGehee also reported that the charge transport behavior of conjugated polymers is a determinative feature to photovoltaics and thin‐film transistors.…”
Section: Resultsmentioning
confidence: 99%
“…One of the aims of this study is to produce PTh/Co 3 O 4 nanocomposites with low cost, high conductivity and high thermal stability so that they can be used in various electronic applications. For instance, Li et al and Ashraf et al showed that PTh based composites with high conductivity can be used in polymeric memory devices, Li‐ion battery components and microelectronics. Another probably more important aim is to determine the ideal charge transport mechanism model of the PTh and its nanocomposites, which is important for developing new materials for various applications mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Stretchable polymer-based resistive memories were an alternative to conventional inorganic semiconductor-based memory, due to their good flexibility for wearable device, [2,3] low cost, ease of processability, [4] and good scalability. [15] A number of polymeric materials, including polythiophene, [16] polyaniline, [17] polypyrrole, [18] poly(9-vinylcarbazole), [19] and poly(methyl methacrylate) [20] had been explored for polymer memory effects and applications. [15] A number of polymeric materials, including polythiophene, [16] polyaniline, [17] polypyrrole, [18] poly(9-vinylcarbazole), [19] and poly(methyl methacrylate) [20] had been explored for polymer memory effects and applications.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] These merits further accelerated the development of several types of polymer-based memory devices such as rewritable memory, [10][11][12][13] flash type, write once read many times (WORM)type memory, [14] and dynamic random access memory (DRAM). [15] A number of polymeric materials, including polythiophene, [16] polyaniline, [17] polypyrrole, [18] poly(9-vinylcarbazole), [19] and poly(methyl methacrylate) [20] had been explored for polymer memory effects and applications. Almost the entire aforementioned were utilized as polyelectrolytes, dye matrices, or component of a charge-transfer complex in a doping or blending system.…”
mentioning
confidence: 99%